Delamination of multilayer graphene stacks from its substrate through wrinkle formation under high pressures. (15th November 2021) - Amaral, I.R.; Forestier, A.; Piednoir, A.; Galafassi, R.; Bousige, C.; Machon, D.; Pierre-Louis, O.; Alencar, R.S.; Souza Filho, A.G.; San-Miguel, A.
Abstract: There is a need to find new paths for van der Waals 2D-systems detachment and transfer or to control their adhesion state in different environments. We have observed that supported multilayer graphene immersed in a fluid can be detached from a substrate through pressure application. The process is based on the development of wrinkles originated by the difference of in-plane-compressibility between the graphene stacks and the substrate. Graphene stacks comprised between 9 and 110 layers and immersed in various fluids allowed to investigate the growth and evolution of wrinkles with increasing pressure. The detachment from the substrate stops at the pressure-induced fluid solidification. Methanol, ethanol or their mixtures favor the pressure-induced wrinkle formation in SiO2 /Si substrates. In these cases, the pressure evolution of the delamination process follows a universal behavior independently of the number of graphene layers with a complete delamination at ∼ 4GPa. The quantitative analysis of the wrinkle geometry evolution can be consistently interpreted as due to a pressure-induced increase of the bending stiffness of the graphene stacks, or a reduction of the adhesion forces between the sample and the substrate, or both. These results should also be of practical use in high-pressure experiments of van der Waals systems. Graphical abstract: Image 1